Organ transplants and the cost-benefit of medical progress - Fiori, Angelo (Medicina e Morale, 2024)
For some time now, the issue of organ transplants has been re-proposed to public opinion after a period of relative silence that followed the season of great interest that marked its beginnings. Attention is mainly focused, as in the past, on the difficulties in finding suitable donors and organs, which in our country make the statistics take a back seat, while elsewhere the numbers are growing and the results seem satisfactory.